MEMBANGUN KARAKTER ANAK PADA LITERASI MELALUI PROGRAM FUN SCHOOLING DI SD NEGERI DESA PANDANMULYO - Denna Delawanti Chrisyarani; Binti Puji Rahayu; Asa Mufngidatul Ilmiyah; Elsa Amelia Irawan; Jihan Faradillah; Sinta Maliha; Dian Fisesa; Adhe Syahrul Yanuar (Fakultas Ilmu Sosial dan ilmu Politik, 2022)
An educational innovation is very much needed in improving the quality of education, with the hope that this innovation will be able to achieve the expected educational goals and form virtuous character for students. Thematic Real Work Lectures (KKNT) are one form of learning by providing learning experiences to students. students in the midst of community life by participating in helping solve problems based on scientific competence. KKNT provides a forum for students to contribute all the knowledge they have learned in lectures in the community, one of which is literacy problems for students at SDN 1 Pandanmulyo and SDN 2 Pandanmulyo. Efforts to increase character in building the literacy skills of students are carried out by procuring a Fun Schooling activity program which aims to make students more enthusiastic in developing literacy characters and abilities. The method used in this research is the method of observation (observation) and the method of interview (interview). This is proven by the implementation of the program, that the enthusiasm of the students in the Fun Schooling program which aims to improve the literacy skills of students through nature-based schools. Efforts to improve literacy skills in this program are said to be going very well after seeing the responses from various parties regarding the implementation of the program, and the school.